DAMPAK PENGGUNAAN E-WALLET TERHADAP EFISIENSI PENGELOLAAN KEUANGAN DENGAN DIMODERASI OLEH DIGITAL NATIVE PADA GEN Z - Lisnayanti, Ni Wayan Sri; Sukma, Paradisa (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2025)
The development of fintech in Indonesia has changed the conventional business model into a moderate business. One technology that is increasingly popular among Gen Z is e-wallet. The increasing use of e-wallet among Gen Z shows the high adoption of financial technology, thus influencing their financial decisions to be faster and more practical. This study aims to examine the influence of e-wallet and the moderating role of digital natives on the efficiency of Gen Z's financial management. This study uses an associative research method with a quantitative approach. The respondents in this study were 233 students. Data were processed using the Partial Least Square (PLS) technique with the SmartPLS 4.0 application. The results of this study reveal that e-wallet has a positive effect on the efficiency of Gen Z's financial management. The influence of e-wallet is strengthened by the role of digital natives as moderation. The implications of this study indicate that e-wallet can increase the efficiency of financial management, which provides benefits for technology developers, educational institutions, and policy makers (government) to support digital financial literacy among Gen Z.